2008
DOI: 10.1161/circep.108.788349
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Perinatal Variant of Long-QT Syndrome Caused by a Profoundly Dysfunctional Cardiac Sodium Channel

Abstract: Background-Inherited cardiac arrhythmia susceptibility contributes to sudden death during infancy and may contribute to perinatal and neonatal mortality, but the molecular basis of this risk and the relationship to genetic disorders presenting later in life is unclear. We studied the functional and pharmacological properties of a novel de novo cardiac sodium channel gene (SCN5A) mutation associated with an extremely severe perinatal presentation of long-QT syndrome in unrelated probands of different ethnicity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
2

Relationship

4
4

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 48 publications
3
46
0
Order By: Relevance
“…The most common cause is long-QT syndrome, with most of these infants having significant QT prolongation. [6][7][8] Among infants with normal resting ECGs, Brugada or Brugada-like syndrome seems to be the most common cause, [2][3][4] although some of these infants may demonstrate intermittent ST changes or intraventricular conduction delay. Kanter et al 2 found disease-causing mutations in SCN5A or CaCNB2b channels in 5 infants with ventricular tachycardia or VF, in whom a diagnosis could not be initially determined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common cause is long-QT syndrome, with most of these infants having significant QT prolongation. [6][7][8] Among infants with normal resting ECGs, Brugada or Brugada-like syndrome seems to be the most common cause, [2][3][4] although some of these infants may demonstrate intermittent ST changes or intraventricular conduction delay. Kanter et al 2 found disease-causing mutations in SCN5A or CaCNB2b channels in 5 infants with ventricular tachycardia or VF, in whom a diagnosis could not be initially determined.…”
Section: Discussionmentioning
confidence: 99%
“…1 Infants with this dramatic presentation are often diagnosed with a cardiac tumor, metabolic disorder, or primary electric disease. [2][3][4][5][6][7][8][9] There have been no previous reports of young infants with ventricular fibrillation (VF) in which a primary diagnosis could not be determined. We present 3 unrelated infants <2 months of age who survived VF arrests.…”
mentioning
confidence: 99%
“…Some evidence points to more severe arrhythmia consequences of SCN5A mutations. 68 In general, male patients experience their first cardiac events at a younger age than female patients. 69 Approximately 90% of first cardiac events occur before the age of 15 years in male patients, particularly in males with LQT1, whereas female patients rarely experience their first cardiac event occasionally after the age of 20 years.…”
Section: Clinical Coursementioning
confidence: 99%
“…I Na was recorded from HEK-293 cells that expressed SCN5A or SCN5A-GFP using the whole cell patch-clamp technique as previously described (37). In brief, the bath solution contained (in mmol/l) 145 NaCl, 4 KCl, 1.8 CaCl 2, 1 MgCl2, 10 HEPES, and 10 glucose (pH 7.35, adjusted with NaOH).…”
Section: Methodsmentioning
confidence: 99%
“…Electrode resistance ranged from 0.8 to 1.5 M⍀. From a holding potential of Ϫ120 mV, standard voltage-clamp protocols were used to examine the voltage dependence of channel activation, steadystate availability, and recovery from fast inactivation (37). For pharmacological experiments, PMA was freshly prepared before experiments from 100 M stock solutions stored at Ϫ20°C.…”
Section: Methodsmentioning
confidence: 99%